FERTILIZERS - INFORMATION TECHNOLOGY OPTIMUM PRODUCTION CONTROL - Корниенко, Б.Я. (Science-based technologies, 2015)
This article describes the basic principles of information technology, management of production of mineral fertilizers, which will combine the following hardware, software and organizational and methodological tools: mathematical models of the installation process research, process optimization, security system and automatic control system. On the basis of the proposed information technology optimal control decided the new scientific and applied problems, namely increased efficiency of processes of granular fertilizers with the requirements of energy efficiency, ensure the specified quality of the finished product and increased uptime of equipment. A new approach - the ideology of automated problem solving, considering information technology as part of manufacturing of fertilizers, as a set of class methods, which in contrast to the ACS, flexible use of various kinds of components and software, depending on many substantive problems to be solved.